2018
DOI: 10.1152/ajprenal.00619.2016
|View full text |Cite
|
Sign up to set email alerts
|

Connecting tubule glomerular feedback mediates tubuloglomerular feedback resetting after unilateral nephrectomy

Abstract: Unilaterally nephrectomized rats (UNx) have higher glomerular capillary pressure (P) that can cause significant glomerular injury in the remnant kidney. P is controlled by the ratio of afferent (Af-Art) and efferent arteriole resistance. Af-Art resistance in turn is regulated by two intrinsic feedback mechanisms: 1) tubuloglomerular feedback (TGF) that causes Af-Art constriction in response to increased NaCl in the macula densa; and 2) connecting tubule glomerular feedback (CTGF) that causes Af-Art dilatation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…SNGFR is influenced by various intrarenal mechanisms including glomerular capillary pressure, single nephron plasma flow, and tubuloglomerular feedback (TGF) ( Blantz and Pelayo, 1984 ). The rise in SNGFR and glomerular capillary pressure following reduction in kidney mass has been associated with a reduction in afferent arteriole resistance and a right-ward shift in TGF ( Müller-Suur et al, 1980 ; Salmond and Seney, 1991 ; Brown et al, 2011 ; Monu et al, 2018 ). It has been suggested that the right-ward shift results in blunting (resetting) of TGF where significantly higher fluid flow rates are required to cause a TGF mediated inhibition of SNGFR ( Salmond and Seney, 1991 ).…”
Section: Mechanisms Facilitating Adaptations and Potentiating Kidney mentioning
confidence: 99%
See 1 more Smart Citation
“…SNGFR is influenced by various intrarenal mechanisms including glomerular capillary pressure, single nephron plasma flow, and tubuloglomerular feedback (TGF) ( Blantz and Pelayo, 1984 ). The rise in SNGFR and glomerular capillary pressure following reduction in kidney mass has been associated with a reduction in afferent arteriole resistance and a right-ward shift in TGF ( Müller-Suur et al, 1980 ; Salmond and Seney, 1991 ; Brown et al, 2011 ; Monu et al, 2018 ). It has been suggested that the right-ward shift results in blunting (resetting) of TGF where significantly higher fluid flow rates are required to cause a TGF mediated inhibition of SNGFR ( Salmond and Seney, 1991 ).…”
Section: Mechanisms Facilitating Adaptations and Potentiating Kidney mentioning
confidence: 99%
“…Thus, this resetting of TGF permits the increase in SNGFR and increase in glomerular capillary pressure in the remaining nephrons following nephron loss. In the rat, resetting of TGF 24 h after unilateral nephrectomy is mediated by enhanced connecting tubule glomerular feedback (a feedback system that influences afferent arteriole dilatation and is associated with epithelial sodium transporter; ENaC) ( Monu et al, 2018 ). This resetting of TGF also sustains the increase in glomerular capillary pressure observed following 5/6th and unilateral nephrectomy in the rat ( Salmond and Seney, 1991 ).…”
Section: Mechanisms Facilitating Adaptations and Potentiating Kidney mentioning
confidence: 99%
“…This compensation includes an increase in the single nephron GFR and subsequent glomerular and tubular hypertrophy. After UNx, TGF is reset, and CTGF is very active [29]. The inhibition of CTGF after UNx restored the TGF response.…”
Section: Connecting Tubule-glomerular Feedback Modulates Tgfmentioning
confidence: 99%
“…These results indicate that at least part of the TGF resetting is due to the CTGF that modulates the TGF response. More dramatic TGF resetting is observed in the remnant kidney after unilateral nephrectomy (UNx) [29]. When renal parenchyma is reduced, the remnant nephron must compensate by increasing the amount of sodium and water excretion.…”
Section: Connecting Tubule-glomerular Feedback Modulates Tgfmentioning
confidence: 99%
“…Thus, for the same amount of Na ϩ in the MD, the vasoconstriction response is much less. This phenomenon is called TGF resetting and occurs in physiological and pathophysiological conditions, including in response to growth (9), pregnancy (5), unilateral nephrectomy (Unx) (26,28), increased NaCl intake, increased fluid volume (10), etc. These situations represent states where high Na ϩ excretion is needed and inappropriately high TGF activity could lead to salt and water retention.…”
Section: Interaction Between Tgf and Ctgfmentioning
confidence: 99%